(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Maraging steels are martensitic steels hardened by precipitation of intermetallic compounds in thermal aging, with good machining properties and high strength, fracture toughness and corrosion resistance, being used in aircraft parts and rocket motor-case, tooling applications and nuclear plants. During thermal aging in steam atmosphere a protective and corrosion resistant oxide layer is formed over the bulk. In this work, conventional Bragg-Brentano geometry was used to identify the phases formed in four specimens of maraging steel grade 300 with different surface finishes that were previously solution annealed twice at (950 ± 5) °C for 1 h, air-cooled, and submitted to oxidation process under positive pressure about 1.5 kPa of steam at (480 ± 5) °C for 6 h, followed by forced air-cooling. Diffraction patterns were measured employing CuKα radiation, ranging 20º < 2θ < 85º and the Rietveld method was used to better characterize the structures identified. Through Rietveld refinements it was possible to conclude that the layer formed during heat treatment process is constituted by a transition metallic phase with a quasi-cubic face centered unit cell, and an oxide layer that includes hematite, magnetite and a spinel structure type MFe2O4, where M could be an alloying element, for all analyzed samples.